Colorectal cancer susceptibility loci as predictive markers of rectal cancer prognosis after surgery. Issue 3 (28th November 2017) - Hu, Yue; Gaedcke, Jochen; Emons, Georg; Beissbarth, Tim; Grade, Marian; Jo, Peter; Yeager, Meredith; Chanock, Stephen J.; Wolff, Hendrik; Camps, Jordi; Ghadimi, B. Michael; Ried, Thomas
Abstract: To understand the molecular mechanism of rectal cancer and develop markers for disease prognostication, we generated and explored a dataset from 243 rectal cancer patients by gene expression microarray analysis of cancer samples and matched controls, and SNP‐arrays of germline DNA. We found that two of the loci most strongly linked with colorectal cancer (CRC) risk, 8q24 (upstream of MYC ) and 18q21 (in the intron of SMAD7 ), as well as 20q13 (in the intron of LAMA5 ), are tightly associated with the prognosis of rectal cancer patients. For SNPs on 18q21 (rs12953717 and rs4464148) and 20q13 (rs4925386), alleles that correlate with higher risk for the development of CRC are associated with shorter disease free survival (DFS). However, for rs6983267 on 8q24, the low risk allele is associated with a higher risk for recurrence and metastasis after surgery, and importantly, is strongly correlated with the resistance of CRC cell lines to chemoradiotherapy (CRT). We also found that although MYC expression is dramatically increased in cancer, patients with higher levels of MYC have a better prognosis. The expression of SMAD7 is weakly correlated with DFS. Notably, the presence of the 8q24 and 18q21 SNP alleles is not correlated with expression levels of MYC and SMAD7 . rs4464148, and probably rs6983267 and rs4925386, are linked with overall survival time of patients. In conclusion, we show that several CRC risk SNPs detect subpopulations of rectal cancer patients with poor prognosis, and that rs6983267 probably affects prognosis through interfering with the resistance of cancer cells to CRT.